Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1073/pnas.91.26.12828
|View full text |Cite
|
Sign up to set email alerts
|

Subunit stoichiometry of staphylococcal alpha-hemolysin in crystals and on membranes: a heptameric transmembrane pore.

Abstract: Elucidation of the accurate subunit stoichiometry of oligomeric membrane proteins is fraught with complexities. The interpretations of chemical cross-linking, analytical ultracentrifugation, gel filtration, and low-resolution electron microscopy studies are often ambiguous. Staphylococcal a-hemolysin (crHL), a homooligomeric toxin that forms channels in cell membranes, was believed to possess six subunits arranged around a sixfold axis of symmetry. Here, we report that analysis of x-ray diffraction data and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(178 citation statements)
references
References 41 publications
8
169
0
Order By: Relevance
“…Staphylococcal Ī±-hemolysin forms heptamers in solution with the oligomeric forms embedding in the host red blood cell membrane to cause lysis (5). Our studies demonstrated that Ī±-hemolysin was unable to bind to red blood cells in the presence of GML, suggesting that the primary effect of GML was to stabilize red blood cell membranes and block the binding of Ī±-hemolysin to red blood cell membranes.…”
Section: Discussionmentioning
confidence: 75%
“…Staphylococcal Ī±-hemolysin forms heptamers in solution with the oligomeric forms embedding in the host red blood cell membrane to cause lysis (5). Our studies demonstrated that Ī±-hemolysin was unable to bind to red blood cells in the presence of GML, suggesting that the primary effect of GML was to stabilize red blood cell membranes and block the binding of Ī±-hemolysin to red blood cell membranes.…”
Section: Discussionmentioning
confidence: 75%
“…This toxin, which has little sequence homology to aerolysin but shares a similar mode of action, was thought previously to form hexamers or tetramers based on electron microscopy [11], analytical centrifugation, cross-linking and SDS-PAGE analysis, [12,13]. However, X-ray analysis of crystals and an elegant charge shift migration assay have recently provided convincing evidence that alpha toxin forms a heptamer [32]. It has also been recently reported that the oligomeric forms of the protective antigen of anthrax toxin [33] as well as that of Vac A from Helicabacter pylori (R. Rappuoli, personal communication) are both heptamers.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the electrophoretic migration, ā£-HL(3-293) was proposed to form a pentamer. Recently, the number of ā£-HL monomeric units present in the oligomer was revised from six to seven (23), and hence, the earlier conclusion that the ā£-HL(3-293) mutant forms a pentameric structure is no longer tenable. As discussed later, data presented here clearly show that the oligomer of ā£-HL(5-293) comigrates with the oligomer of ā£-HL (see Fig.…”
Section: Membrane-bound Monomer 3mentioning
confidence: 99%